REDUCTION EXTRACTION KINETICS OF TITANOMAGNETITE CONCENTRATE BY CARBON MONOXIDE - Sun, Haoyan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Titanomagnetite concentrate was reduced by CO-Ar gas mixtures in a laboratory fixed bed reactor in the temperature range from 1123 to 1323 K. The influences of reductive conditions on the reduction rate and metallization degree including reduction temperature, reduction time and carbon monoxide content were studied. And the characteristics of reduced samples were analyzed by XRD, BES and EDS. Results shown that both the reduction and metallization degree increased with the increasing of temperature and monoxide content. The low reduction degree was owing to the low iron oxides content and high impurities content such as magnesium oxide in titanomagnetite concentrate. Above 1123 K, the reduction is controlled by interfacial chemical reaction at early stage of the reaction and then turns to the internal diffusion controlling with reaction processing. The reduction path at temperatures above 1123 K is suggested as follow: (please see the formula edited by MathType in the manuscript )